Management der sozialen Verantwortung im Krankenhaus Corporate Social Responsibility als nachhaltiger Erfolgsfaktor - Naegler, Heinz (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2011)
"Caritas, which is inherent in health care, is also not a countercategory to economy, i.e. to economic activity, just as the management of social responsibility is not limited to the moderation (apparently) opposing interests of patients, employees and providers. On the contrary: In the hospital - as in any other business organization - social responsibility must be defined as a strategic task to strengthen competitiveness and manage changes and to be implemented permanently in terms of personnel and institutions. - How can the actors in a hospital assume and implement social responsibility and at the same time ensure sustainable performance? - Who are the different stakeholders and which positions and aspects have to be taken into account in which business decisions? - What are the measures for socially responsible action and thus the target values ​​and fields of action of the responsible persons? - What are the personnel and institutional requirements for managing social responsibility? These questions are presented in an implementation-oriented manner and supplemented by practical examples for the development and implementation of a new management of social responsibility."